Private Leadership in Developing the Religious Culture of Setia Budi Abadi Perbaungan High School - Fitri yulia; Atika Hanan Julia Harahap; Putri Syahri (Edumaspul: Jurnal Pendidikan, 2023)
The principal is a leader in the school, the principal is very influential in developing religious culture in the school environment. There are many religious cultures that must be developed, especially in terms of the effectiveness and efficiency of fostering religious culture in schools and society. Therefore the principal seeks to develop a religious culture in school by increasing the religious atmosphere so that students are accustomed to behaving in accordance with Islamic values. Researchers use qualitative methods with descriptive methods. Data collection techniques using; (1) Interview, (2) Observation, (3) Documentation. The data analysis used by the author is triangulation. The focus of the writer's research is; (1) The principal's vision and mission in developing a religious culture, (2) The principal's way of developing a religious culture Keywords: Leadership, Religious Culture